A review: Biodegradation of resin-dentin bonds - Masanori Hashimoto; Futami Nagano; Kazuhiko Endo; Hiroki Ohno (Elsevier, 2011)
Resin-dentin bonding was first achieved through mechanical hybridization between resin and collagen fibrils using a functional monomer containing resin system. In the last decade, new adhesive resin systems were frequently released onto the market within a short-period of time. Before and after commercialization, the bond integrity has been tested by bond tests, and leakage evaluation by researchers, but it is very difficult for clinicians to obtain a comprehensive, up-to-date understanding of their nature and degradation. Although newly developed adhesive resins have attempted to improve the bond strength at least in the first 24 h after bonding, the long-term durability of the bonds has not yet been established analytically. However, numerous recent studies have shown micromorphological evidence of biodegradation of resin-dentin bonds, due to hydrolysis of the resin and collagen fibrils within the bonds. This review mainly summarizes the most recent work in biodegradation of resin-dentin bonds based on micromorphological analyses of data obtained by scanning and transmission electron microscopy.